Current Practices and Attitudes Regarding Use of Inhaled Nitric Oxide in the NICU: Results From a Survey of Members of the National Association of Neonatal Nurse Practitioners. (April 2018) - Kayton, Allyson; Timoney, Paula; Vargo, Lyn; Perez, Jose A.
Abstract : Background: Excessive supplemental oxygen exposure in the neonatal intensive care unit (NICU) can be associated with oxygen-related toxicities, which can lead to negative clinical consequences. Use of inhaled nitric oxide (iNO) can be a successful strategy for avoiding hyperoxia in the NICU. iNO selectively produces pulmonary vasodilation and has been shown to improve oxygenation parameters across the spectrum of disease severity, from mild to very severe, in neonates with hypoxic respiratory failure associated with persistent pulmonary hypertension of the newborn. Purpose: An online survey was conducted among members of the National Association of Neonatal Nurse Practitioners to gain insight into the level of understanding and knowledge among neonatal nurse practitioners (NNPs) about optimizing supplemental oxygen exposure and the use of iNO in the NICU setting. Results: Of 937 NNP respondents, 51% reported that their healthcare team typically waits until the fraction of inspired oxygen level is 0.9 or more before adding iNO in patients not responding to oxygen ventilation alone. Among respondents with 1 or more iNO-treated patients per month, only 35% reported they know the oxygenation index level at which iNO should be initiated. Less than 20% of NNPs reported perceived benefits associated with early initiation of iNO for preventing progression to use of extracorporeal membrane oxygenation or reducing the length of hospital stay, and about one-third of respondents reported they believe early iNO use minimizes hyperoxia. Implications for Practice: More education is needed for NNPs regarding the negative effects of oxidative stress in neonates. Implications for Research: Additional clinical trials investigating the most beneficial strategies for avoiding neonatal hyperoxia are warranted.